STUDY ON COMMUNITY KNOWLEDGE (HAPPINIMAL PROJECT) IN MANAGING ORGANIC AGRICULTURAL AND LIVESTOCK WASTE - Maharani, Nadia; Rejeki, Desi; Malik, Amalia; Susanti, Susanti; Halimah, Nur (Universitas Sintuwu Maroso, 2025)
The management of organic agricultural and livestock waste remains a challenge in society, primarily due to a lack of understanding regarding its potential for valuable and sustainable utilization. Organic waste is often perceived as mere refuse with no functional value, resulting in suboptimal management. This study aims to evaluate the level of public knowledge concerning the processing of organic agricultural and livestock waste, as well as the changes in knowledge following educational intervention. The research method employed was an online survey conducted via the social media platform Instagram, involving 2,048 respondents from the general public. The research instrument consisted of pre-test and post-test questionnaires covering five key indicators related to the utilization of organic agricultural and livestock waste. The results showed that the average knowledge level of respondents in the pre-test was 67.6%, which increased to 90.2% in the post-test, representing an improvement of 22.6%. The highest increase occurred in the indicator for utilizing animal waste as biogas and organic fertilizer, which reached 100%. These findings indicate that education delivered contextually and according to community needs can significantly enhance public understanding. This increase in knowledge is expected to serve as a foundation for fostering awareness and encouraging the implementation of independent, sustainable, and economically valuable waste management.